Clima organizacional y desempeño laboral en la Unidad de Gestión Educativa de Maynas Loreto área de gestión pedagógica 2024 - Acho Santillan, Jery (2025)
The research focused on describing and analyzing how different variables are related, using numerical data and observing a specific group only once, without intervening. The results showed a strong connection between the variables, with a Spearman correlation coefficient of 0.887**, and a very high significance level (0.000), indicating that this relationship is direct and reliable. In summary, it is evident that a positive organizational climate beneficially influences employees' job performance, promoting higher levels of effectiveness, efficiency, initiative, and competence. This highlights the importance of a good work environment for improving job performance.